Picture Puzzle Media Improves Tenth Grade Students’ Speaking Skill: Media Teka-teki Gambar Meningkatkan Kemampuan Berbicara Siswa Kelas X - Nurani, Sevya Dwi Gita; Santoso, Dian Rahma (Indonesian Journal of Education Methods Development, 2025)
General background: Speaking skill is a crucial component of English language proficiency and often becomes a major challenge for students due to anxiety, lack of preparation, and limited vocabulary. Specific background: In many classrooms, conventional methods such as repetition or memorization are less effective in encouraging active participation and confidence. Knowledge gap: Limited studies have explored the role of visual and kinesthetic media, particularly picture puzzles, in strengthening students’ speaking performance. Aim: This study investigates the use of picture puzzle media to improve speaking skills of tenth-grade students at SMA Muhammadiyah 4 Porong. Results: Employing a pre-experimental quantitative design with pre-test and post-test, findings reveal a significant increase in students’ average speaking scores from 75.27 to 88.18 after the treatment. Novelty: The integration of picture puzzles as learning media fosters both creativity and confidence, especially for kinesthetic learners, by linking visual storytelling with oral expression. Implications: These results suggest that picture puzzles can serve as an innovative pedagogical tool in EFL classrooms, providing teachers with practical strategies to reduce speaking anxiety and support students’ active communication. Highlights: Picture puzzles improve speaking performance significantly. Media supports kinesthetic and visual learning styles. Reduces student anxiety in oral activities. Keywords: Speaking skill; Picture Puzzle; EFL Classroom; Kinesthetic Learning; Narrative Text